Addison crisis related psychosis - A. Papanastasiou; A. Roubi; L. Tsitrouli; A. Antoniou; G. Vouraki; E.T. Tsapardoni; V. Drakuli; S.M. Papageorgiou; A. Pahi (European Psychiatry, 2022)
Introduction Addison’s disease (AD) is a rare disorder of the adrenal glands which causes deficiency of cortisol and aldosterone. It presents with a variety of symptoms, including neuropsychiatric manifestations. We discuss the case of a patient who exhibited psychotic symptoms in clear consciousness and no other clinical sign of AD.